PENGARUH PENDEKATAN ILMIAH DALAM PEMBELAJARAN FISIKA TERHADAP KETERAMPILAN PROSES SAINS PESERTA DIDIK KELAS X SMAN 1 MARIORIWAWO KABUPATEN SOPPENG - Tiara Purnama; Abdul Haris; Muhammad Arsyad (Universitas Negeri Makassar, 2015)
This research is a quasi-experimental with static group comparison design with the aims are to determine; 1) the magnitude of science process skills of students who are taught by a scientific approach; 2) the amount of science process skills of students who are taught without scientific approach; 3) significant difference to the science process skills of students who are taught by a scientific approach with which taught without using a scientific approach; The variables studied were scientific approach as independent variables, science process skills as dependent variables. The population in this study was all students of class X of SMAN 1 Liliriaja Academic Year 2014/2015. Based on the results of the descriptive analysis showed that the Science Process Skills Learners are taught with scientific approaches is higher than the learners who are taught without using a scientific approach. Inferential analysis shows that there are significant differences on Science Process Skills Learners were taught through a scientific approach with learners who are taught without scientific approach.Telah dilakukan penelitian eksperimen semu yang bertujuan untuk memperoleh gambaran 1) besarnya keterampilan proses sains peserta didik yang diajar dengan pendekatan ilmiah; 2) besarnya keterampilan proses sains peserta didik yang diajar tanpa pendekatan ilmiah; 3) perbedaan yang signifikan terhadap keterampilan proses sains peserta didik diajar dengan pendekatan ilmiah dengan yang diajar tanpa mengunakan pendekatan ilmiah. Populasi dalam penelitian ini adalah seluruh peserta didik kelas X SMAN 1 Liliriaja Tahun Ajaran 2014/2015. Berdasarkan hasil analisis deskriptif didapatkan bahwa keterampilan proses sains peserta didik yang diajar dengan pendekatan ilmiah lebih tinggi daripada peserta didik yang diajar tanpa menggunakan pendekatan ilmiah. Analisis inferensial menunjukkan bahwa terdapat perbedaan signifikan terhadap keterampilan proses sains peserta didik diajar melalui pendekatan ilmiah dengan peserta didik yang diajar tanpa pendekatan ilmiah.Kata Kunci: keterampilan proses sains, pendekatan ilmiah